Assessment of the Performance of a Water Treatment Plant in Ecuador: Hydraulic Resizing of the Treatment Units - Mejía Bustamante, Lisbeth (2022)
Granting access to drinking water has been a challenge because 47% of the worldwide population is not connected to a drinking water distribution network in rural settlements. This study aimed to evaluate the contaminant removal efficiency in a conventional water treatment facility in the Austro region of Ecuador, Paute, to identify the treatment units requiring hydraulic resizing. Water samples were collected from each treatment unit to characterize the physical-chemical and microbiological parameters, and the dimensions of the treatment ponds for hydraulic evaluation purposes. Water hardness, electrical conductivity, SO42−, and Fe2+ were the main issues found in the water, which failed to comply with Ecuadorian technical guidelines. The treatment units, such as the flocculator, rapid sand filter, and storage tank, were resized to meet the demand of the future population. In addition, the residual free chlorine was measured as insufficient in the community’s tap water, showing an unprotected water distribution system to microbiological contamination. No disinfection by-products were found despite the existence of biodegradable organic matter. The findings of this research propose improvements in the deployed treatment practices to provide the community with drinking water in accordance with the Sustainable Development Objectives (SDG 3 and SDG 6).